Motivasi Siswa dalam Mengikuti Kegiatan Ekstrakurikuler Pencak Silat di SDN Kembangarum 02 Kota Semarang - Sholeh, Muhammad; Winarno, Imam Santosa Ciptaning Wahyu (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to find out what is the students’ motivation in participating in pencak silat extracurricular at SDN Kembangarum 02 Semarang City. The data collection used in this study is observation method, questionnaires and documentation. Checking the validity of the datum used triangulation techniques. The result shows that the students' motivation in participating in pencak silat extracurricular at SDN Kembangarum 02 Semarang City in the very high category is an indicator of trainer with a total score 714 and the average is 17.85. In the second place is an indicator of interest with a total score 699 and the average is 17.47. In the third place is the physical indicator with a total score 695 and the average is 17.37. In the fourth place is the indicator of motive with a total score 692 and the average is 17.3. The fifth is the indicator of environmental with a total score 684 and the average is 17.1. The sixth is the indicator of facilities and infrastructure with a total score 673 and the average is 16.82. In the seventh place is indicator of family with a total score 672 and the average is 16.8. The eighth is the indicator of talent with a score 632 and the average is 15.8.The conclusion of this study is it is good for the trainer to always provide motivation, good training, variety, interesting and look for students who have strong.